Latent profile analysis of parental burnout among parents of children with and without autism spectrum disorder - Shuyu Liu; Dehua Wu; Jibo Li; Huazhan Yin (Frontiers in Psychology)
BackgroundParental burnout is an emerging global focus on parental mental health and parenting practices. However, parental burnout among parents of children with autism spectrum disorder (ASD) in China remains largely unexplored.ObjectiveThis study aimed to identify differences in parental burnout severity and patterns between Chinese parents raising children with and without ASD, while exploring key sociodemographic factors contributing to these disparities.MethodsIn total, 1,048 Chinese parents (including 487 parents of children with ASD) were recruited to take part in an online survey. The participants completed the Chinese version of Brief Parental Burnout Assessment and Brief Demographic Questionnaire. For data analysis, Latent Profile Analysis (LPA) was employed to identify distinct burnout profiles, followed by multivariate logistic regression to examine the association between sociodemographic factors and profile membership.ResultsThe LPA revealed distinct classification patterns between the two groups: parents of children with ASD demonstrated three subgroups (Low, Medium, and High parental burnout profiles), while parents of children without ASD exhibited only two subgroups (Low, Medium parental burnout profiles). Multivariate logistic regression analysis found that mothers, parents with two or more children, parents with younger children, and parents of children with severe ASD were associated with high parental burnout profiles.ConclusionParents of children with ASD were more likely to experience higher levels of parental burnout. It highlights an urgency for targeted interventions to different burnout subgroups of parents having children with ASD.